Synthesis, Characterization, and Antibacterial Activity of Lanthanide Metal Complexes with Schiff Base Ligand Produced from Reaction of 4,4-Methylene Diantipyrine with Ethylenediamine - Kawther Adeeb Hussein; Naser Shaalan (Universitas Gadjah Mada, 2022)
An environmentally friendly method for the synthesis of Schiff bases was described by combining 4,4-methylenediantipyrine with ethylenediamine. The complex was prepared in a classical way, the usual condensation reaction method. A series of metal complexes were prepared from reactions of lanthanide nitrate salts [Nd+3, La+3, Er+3, Gd+3, and Dy+3] with a Schiff base ligand. The structures of the complexes were confirmed by analytical studies, spectral measurements, and thermal studies, and the prepared ligand was characterized using microanalysis technique, UV-Visible, infrared, nuclear magnetic resonance 1H-NMR and 13C-NMR, mass spectrometry, and thermogravimetric analysis (TGA), and the addition of conductivity measurement and magnetic moment of complexes. The results showed that these complexes have a consistency of 10 in which the elements are bonded with the ligand through the two nitrogen atoms at C=N and that the bonding ratio between the metal:ligand is in 1:2 ratio. By using agar disc-spreading, we tested several in vitro compounds for their antibacterial activity against four pathogenic bacteria, including Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Klebsiella pneumoniae. The majority of the complexes demonstrated antibacterial activity.